Filosofi Pendidikan Yang diusung Oleh Ki Hadjar Dewantara dan Evolusi Pendidikan di Indonesia - Tia Basana Hutagalung; Liesna Andriany (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The foundation of education is a universal human aspiration; therefore, in addressing educational issues, complex solutions with philosophical foundations are necessary to ensure that the resulting solutions benefit all segments of society. One of the figures with strong philosophical views on education is Ki Hadjar Dewantara. Ki Hadjar Dewantara, a nobleman from the Yogyakarta Sultanate, firmly held a high concern for the development of education. The philosophical views put forward by Ki Hadjar Dewantara have become the basis for educational development in Indonesia. Ki Hadjar Dewantara expressed that the essence of education is an effort to internalize cultural values ​​into the souls of children with the aim of shaping them into complete human beings, both spiritually and mentally. This educational philosophy is known as the "Sistem Among," which emphasizes the basic ability of children to overcome the problems they face by providing them with broad freedom of thought. Ki Hadjar Dewantara formulated his philosophy by applying indigenous Indonesian culture, selectively adopting Western values ​​to fit the trikonic theory, and then adapting them wisely. Ki Hadjar Dewantara also made several contributions to Indonesian education, including the implementation of the leadership trilogy in education, the three educational centers, and the paguron system. Education is an effort to develop the human potential of learners, both physically, intellectually, emotionally, and morally, so that this potential can be realized and beneficial to their lives.